Path tracking control of autonomous vehicles via prescribed performance approach - Zhang, Sucai; Wang, Yongfu; Li, Gang; Wang, Yunlong (Neural computing & applications, 2025)
This paper addresses the path tracking control problem for autonomous vehicles subject to the compound disturbance and unavailable variable. Before the controller design, a state observer and a disturbance observer are constructed to estimate the sideslip angle and the compound disturbance, respectively. Then, a prescribed performance function is proposed to bound the tracking error to improve the tracking accuracy. Finally, the controller is designed based on the backstepping scheme. The Lyapunov stability theory shows that the tracking error converges to a preset range. The effectiveness of the proposed method is verified by hardware-in-the-loop and real vehicle experiments.